The non-Fourier–Fick’s heat and mass flux effect in a bioconvective nanofluid flow over a stretching cylinder with suction/injection and convective conditions - Endale Ersino Bafe; Mitiku Daba Firdi; Lemi Guta Enyadene (Results in Physics)
This study explores the momentum, heat, and mass transfer characteristics of MHD non-Newtonian nanofluids with nanoparticle suspensions containing self-propelled microorganisms over a porous, inclined, and stretching cylindrical surface. The analysis includes the effects of non-Fourier and non-Fick fluxes, suction/injection, convective heat and mass transfer, and motile microorganisms under mixed convection, nonlinear thermal radiation, porosity, Ohmic dissipation, chemical reactions with Arrhenius activation energy, and Brownian motion. The governing equations are transformed into nonlinear ODEs and solved using a spectral local linearization method. Numerical results are illustrated through graphs, tables, contour plots, and 3D visualizations to assess parameter impacts on flow dynamics. Findings reveal that magnetic field intensity, porosity, inertia coefficient, and suction/injection reduce the velocity while increasing temperature. An increase in the thermal Biot number and thermal relaxation time within their ranges enhances surface heat transfer, from 0.1500 to 0.3764 without radiation and from 2.1897 to 4.0690 with nonlinear radiation. Similarly, higher microbial reaction rates and Biot numbers significantly increase microorganism concentration transfer, from 0.158026 to 0.387634, highlighting their substantial impact in applications involving microbial interactions. Further, the inclusion of microorganisms and non-Fickian flux significantly modulates the wall’s drag force. This study advances the understanding of microorganism interactions in radiative and convective Carreau nanofluids, offering insights for industrial and biomedical applications.